Desenvolvimento e aplicação de biorreatores capilares para a triagem de ligantes de Purina Nucleosídeo Fosforilases - Moraes, Marcela Cristina de (Universidade Federal de São Carlos, 2012)
Purine Nucleoside Phosphorylases (PNPs) are key enzymes of the purine salvage pathway, and therefore are considered attractive targets for new drugs search. In this context, the development of effective and selective bioassays for PNP ligands screening is an important task. This work describes the covalent immobilization of human and Schistossoma mansoni PNP on fused silica capillaries. The activity of the immobilized enzyme reactors (IMERs) was monitored on line, employing multidimensional zonal chromatography, by the quantification of the product formed throughout the enzymatic reaction. This method enabled the determination of kinetic constants, screening, identification and characterization of enzymatic inhibitors. Two potent human PNP inhibitors were recognized and characterized. Through the use of inhibitors with different potencies, previously characterized by zonal chromatography, the affinity-based ligands screening employing frontal chromatography was validated. Frontal affinity chromatography analysis demonstrated to be a valuable method for the rapid identification of new ligands, while the main advantage of the multidimensional zonal chromatography method herein described consists on the ability to directly evaluate the effect of the ligands in the biological function of these enzymes. The methods described in this work represent an improvement to the PNPs inhibitors consolidated screening assays, since they directly quantify the enzymatic reaction product or are able to rank the inhibitors according to their affinities, resulting in a rapid automated analysis and false positives free.
Development and application of capillary bioreactors for screening of Purine Nucleoside Phosphorylases ligands
Keywords: Química; Imobilização de enzimas; Ensaios enzimáticos; CIENCIAS EXATAS E DA TERRA::QUIMICA